Efficient DNA operation: Lessons from different DANN settings in non-Annex-B countries - Daisuke Hayashi; Axel Michaelowa (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
As the Clean Development Mechanism (CDM) has shown its rapidly growing market and we approach the beginning of the first commitment period of the Kyoto Protocol, an increasing number of non-Annex-B countries have recently established their Designated National Authorities (DNAs) to participate in the CDM. Essential questions to enable efficient operation of a non-Annex-B DNA (host country DNA) are i) how to expedite an approval process without losing quality of approved projects, ii) how to attract foreign investors, and iii) how to become financially sustainable. It is concluded that a balance between the level of scrutiny and approval speed and criteria is essential for the first question. A standardized and transparent approval process is of great help. As for the second question, a quick and transparent approval process is one of the key factors to attract foreign investors. A careful choice of promotional functions should be made striking a balance between a host country's needs and resource availability. A host country DNA at an early stage of development should first focus on operationalization of its approval system and is not recommended to expand its scope to promotional activities. Concerning the third question, a host country DNA should contemplate a balance among its Certified Emission Reductions (CERs) supply potential, related service fee volumes, and choice of DNA functions.
Keywords: 330; Designated National Authority; Clean Development Mechanism; Kyoto Protocol